Plasmid DNA/RNA separation by ultrafiltration: modeling and application study - Nunes, José C. (2014)
RNA is one of the main soluble contaminants that needs to be separated from plasmid DNA (pDNA) during its recovery process from fermentation broths. Although significantly different in molecular size, pDNA and RNA are difficult to separate by membrane filtration due to the fact that both types of molecules are highly deformable and therefore suffer flow-induced elongation when permeating through porous membranes. The possibility of performing this separation by ultrafiltration is investigated here with the aid of a theoretical model describing the interactions between two electrically charged, flexible macromolecules that simultaneously permeate through a porous membrane. The results of the simulations, applied to pDNA and the different types of RNA present in cell lysates under typical process conditions, show that only by a careful choice of the membrane pore size and the imposed permeate flux one can achieve the required selectivity in this operation. Ultrafiltration tests using microfiltered lysates from the production of two different plasmids, pVAX1-LacZ (6050 bp) and pCAMBIA-1303 (12,361 bp), were carried out to check the validity of the theoretical predictions; the experimental results confirm these predictions and the idea that this technique can be used in practice for pDNA purification.